2020
DOI: 10.1021/acs.jpclett.0c02708
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Free Polymerase Chain Reaction with Triangular Gold and Silver Nanoparticles

Abstract: Photothermal effects of metal nanoparticles (NPs) are used for various biotechnological applications. Although NPs have been used in a polymerase chain reaction (PCR), the effects of shape on the photothermal properties and its efficiency on PCR are less explored. The present study reports the synthesis of triangular gold and silver NPs, which can attain temperatures up to ∼90 °C upon irradiation with 808 nm laser. This photothermal property of synthesized nanoparticles was evaluated using various concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…1f ). 42,43 In contrast, when a similar reaction was performed with protein prepared at pH 2.5, a dramatic change in the morphology of NPs was observed when templated with amyloid fibrils. In this case, predominantly small spherical shape NPs, self-assembled into AuSSs 44 were observed (Fig.…”
Section: Proteins and Their Corresponding Amyloid Forms Modulate The ...mentioning
confidence: 95%
See 2 more Smart Citations
“…1f ). 42,43 In contrast, when a similar reaction was performed with protein prepared at pH 2.5, a dramatic change in the morphology of NPs was observed when templated with amyloid fibrils. In this case, predominantly small spherical shape NPs, self-assembled into AuSSs 44 were observed (Fig.…”
Section: Proteins and Their Corresponding Amyloid Forms Modulate The ...mentioning
confidence: 95%
“…S7b †). 42 To exclude the possibility that at different pHs or during nanocrystal formation, the structure of amyloid fibrils might alter, which in turn may promote different morphological growth of AuNPs, we analyzed the X-ray diffraction of amyloid fibrils. We examined the diffraction patterns before and after the formation of AuTNPs and AuSSs.…”
Section: The Mechanism Of Amyloid Templated Gold Nanoparticles Into D...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Au NPs are characterized by adjustable size and physical size, catalytic activity, high surface volume ratio, high stability, easy synthesis and surface modification, and strong light absorption and scattering properties [5,14]. Figure 1 shows transmission electron microscopy (TEM) images of Au NPs in different morphologies [15,16]. Li et al for the first time reported the optimization of Au NPs on PCR.…”
Section: Utilizing Different Nanomaterials To Enhance Pcr Effectsmentioning
confidence: 99%
“…9,10 Therefore, full-process PCR analysis consumes 1.5-3 hours and relies on bulky equipment and trained professionals, thus requiring systematic optimization for speed, workflow, equipment economy, and convenience. 2,9 Therefore, researchers recently proposed the fusion of microfluidics, 11 fast PCR or isothermal amplification methods, 12 and nanomaterials [13][14][15] to reduce the amplification time and economize devices, 16 and even integrate all processes into one system, giving birth to a "sample-to-answer" concept. 9,[16][17][18][19] For instance, Sumit Kalsi performed microvolume reagent operation and fluorescence recombinase polymerase amplification (RPA) based on an electrowetting on a dielectric-based (EWOD) microfluidic platform and a specialized CCD-based detection device.…”
Section: Introductionmentioning
confidence: 99%